Cultural Landscapes of Energy - Hagemann, Jenny | https://orcid.org/0000-0002-4583-3810; Jacobs, Fabian | https://orcid.org/0000-0002-7937-6515; Laschewski, Lutz | https://orcid.org/0000-0002-5119-0903 (Taylor & Francis, 2026)
This volume explores the contested heritage of landscapes impacted by energy production. It offers a comparative perspective across Europe on different energy resources and reveals the hidden histories behind current efforts to revalorise the industrial heritage of energy production. Including case studies from across the European continent, this volume adds a crucial historical perspective to current debates on energy transition and the future of Europe’s landscapes, which have been deeply impacted by energy production. Coal mining, oil drilling, peat extraction, and the construction of large-scale infrastructure, such as dams, have shaped ‘cultural landscapes of energy’ in present-day Europe. The exploitation of natural resources served economic development and established new industrial work cultures, but it also destroyed settlements through excavation and flooding. This volume brings together conflicting histories around work, habitation, and leisure in contemporary landscapes across Europe. Drawing on archival records, interviews, and fieldwork, the chapters in this volume combine perspectives on the productive and destructive sides of energy. They address the tensions emerging from heritage-making processes, which focus on the end of energy production despite ongoing and future commissioning projects. This volume contributes new insights to the fields of energy and environmental history, heritage studies, memory studies, landscape architecture, and sustainability science. It provides rich materials on energy landscapes across Europe for researchers as well as policymakers and practitioners interested in energy transition, (post-)industrial heritage, and cultural tourism.